Two water-stable 3D supramolecules supported by hydrogen bonds for proton conduction. (1st July 2018) - Chen, Wanyao; Zhao, Lijia; Yu, Shihang; Li, Zifeng; Feng, Junyang; Li, Gang
Graphical abstract: Two substituted imidazole dicarboxylate-based complexes have been solvothermally synthesized, and structurally characterized. Their proton conduction properties have been explored under different temperature and relative humidity, and the proton transfer mechanisms have been proposed. Abstract: By employing the multifunctional organic ligand, 2-(o-bromo)phenyl-4, 5-imidazole dicarboxylic acid (o-H3 BrPhIDC), two three-dimensional supramolecular complexes, [M(o-H2 BrPhIDC)2 (H2 O)2 ]·CH3 CH2 OH·3H2 O (M = Zn (1 ); Co (2 )) have been successfully solvothermally synthesized, and structurally characterized by single crystal X-ray crystallography. Their proton conduction properties have been explored under different temperature and relative humidity (RH). Compounds 1 and 2 indicate high conductivity values of 1.14 × 10 −4  S·cm −1 and 3.11 × 10 −4  S·cm −1, respectively, at 98% RH and 100 °C. The hydrogen bonding nets inside the two complexes perform a vital function in the resultant conductivity. Variable-temperature and Variable-RH experiments of both compounds reveal that the conductivity values increase with increasing temperature and RH. The proton transfer mechanisms of the complexes have been proposed in terms of the structural analyses, activation energy calculations and PXRD determinations.